COMPARATIVE CHARACTERISTICS OF SURGICAL METHODS OF TREATMENT OF DIFFUSE TOXIC GOITER - Khamroev, U.P. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
Background. Surgical treatment, being the oldest way to treat diffuse toxic goiter, still plays an important role in the treatment of patients with this disease. Even though most foreign clinicians prefer radioiodine therapy, some researchers recommend expanding the indications for surgical treatment of diffuse toxic goiter. However, at present, there is no single point of view regarding the scope of surgery for diffuse toxic goiter. Material. Comprehensive examination and treatment of 296 patients with diffuse toxic goiter who were treated and examined in the department of surgery of the Bukhara Regional Multidisciplinary Medical Center. Conclusion. And the analysis of the results of traditional approaches to surgical methods of treating diffuse toxic goiter showed that in 37.5% of cases, good results were achieved. In 46.4% of patients, the treatment results were found to be satisfactory, and in 16% - not satisfactory. One of the terrible complications of operations on the thyroid gland, as shown by the results of our studies, is intra- and postoperative bleeding. This type of complication was noted by us in 26 (14.0%) patients.